A re-engagement model to overcome the psychological distress of students - Meena Ramaswamy; Rajeesh Viswanathan; Byju Kaniyarkuzhi; Sarathlal Neeliyadath (International Journal of Evaluation and Research in Education (IJERE), 2023)
COVID-19 lockdowns and lack of social interaction increased academic disengagement among students in India. This study aims to identify the student engagement pitfalls and the prevalent psychological distress in higher education institutions (HEIs) in India prior to the pandemic and during the same. An exploratory research design is adopted by executing a purposive sampling technique. Researchers collected data from undergraduate students of the top five universities, verified 600 consistent responses, and tested the hypothesis using relevant research tools. Results display that psychological distress (PD) is inversely correlated to student engagement (SE) and negatively impacts it. Researchers introduced a novel re-engagement model called “CAIS”, which is the combination of four variables, creativity, physical activity (PA), internship, service learning (SL), and tested their relationship with PD and SE. Each variable under CAIS shows an inverse correlation with PD and positively impacts SE. This study suggests to include “CAIS” in the curriculum to improve the productivity of students and reduce their stress levels. This investigation is the first of its kind to explore the connection between CAIS, SE, and PD in Indian HEIs. The results contribute to the stakeholders in education to re-engage the students in an innovative pattern during post-pandemic times.